The importance of the economic base theory in urban and regional research - Miszczak, Katarzyna (Znaczenie koncepcji bazy ekonomicznej w badaniach miejskich i regionalnych, 2021)
The article aims to identify the problems faced by urban and regional communities and to provide implementable approaches derived from the economic base theory (EBT). This review essay discusses (often critically) the relevance of EBT to urban and regional research. The article seeks to explore the theoretical implications of the limitations and challenges of basic and non-basic sectors development. The author explored how EBT can increase our understanding of economic processes. A presentation of EBT is followed by a description of the functional structures of cities and regions. The study focused on the evaluation and the application of EBT. The results confirm that EBT has longstanding importance in spatial planning. Although EBT is a simplified abstraction of reality, it can be a helpful platform for the effective implementation of regional (urban) strategies. The original contribution of this paper is to open up the perspective for further research on EBT.
Biblioteka Regionalisty, 2021, Nr 21, s. 92-110
Keywords: economic base theory; urban and regional research; functional structure; teoria bazy ekonomicznej; badania miejskie; badania regionalne; struktura funkcjonalna